2016
DOI: 10.1038/srep21949
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Basis of Oncogenic Mutations G12, G13 and Q61 in Small GTPase K-Ras4B

Abstract: Ras mediates cell proliferation, survival and differentiation. Mutations in K-Ras4B are predominant at residues G12, G13 and Q61. Even though all impair GAP-assisted GTP → GDP hydrolysis, the mutation frequencies of K-Ras4B in human cancers vary. Here we aim to figure out their mechanisms and differential oncogenicity. In total, we performed 6.4 μs molecular dynamics simulations on the wild-type K-Ras4B (K-Ras4BWT-GTP/GDP) catalytic domain, the K-Ras4BWT-GTP–GAP complex, and the mutants (K-Ras4BG12C/G12D/G12V-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
171
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(183 citation statements)
references
References 68 publications
(81 reference statements)
12
171
0
Order By: Relevance
“…However, both the loop regions show significantly lower fluctuations upon nucleotide binding as compared to the nucleotide free state, which signifies the role of these regions in nucleotide binding and/or effector recognition. Earlier simulation studies have shown that mutations in the p-loop or switch regions can significantly alter the degree of flexibility of these regions36373839. A point mutation (P29V) locks the RAC1 in the GTP bound activated state, accompanied by the enhanced flexibility in the SWI region and rigidity in the SWII region36.…”
Section: Resultsmentioning
confidence: 99%
“…However, both the loop regions show significantly lower fluctuations upon nucleotide binding as compared to the nucleotide free state, which signifies the role of these regions in nucleotide binding and/or effector recognition. Earlier simulation studies have shown that mutations in the p-loop or switch regions can significantly alter the degree of flexibility of these regions36373839. A point mutation (P29V) locks the RAC1 in the GTP bound activated state, accompanied by the enhanced flexibility in the SWI region and rigidity in the SWII region36.…”
Section: Resultsmentioning
confidence: 99%
“…Because in the G12D mutation, glycine residue is substituted by aspartate, which has a bulkier side group, it causes a structural change in the P-loop which affects the conformations of the other active site regions SI and SII, as observed in previous studies [22][23][24]59 . Our distance calculations show that after G12D mutation, the P-loop residues 11, 12, 13 move away from SII residue Q61.…”
Section: Discussionmentioning
confidence: 77%
“…Yet, despite decades of research, there are still no drugs in the clinic today that can directly target mutant K-Ras 19,20 . Although the effects of G12D mutation on the structure, conformation and flexibility of K-Ras have been studied [21][22][23][24] , the relationship between its conformational and dynamical changes still remains to be understood. At the same time, there is increasing evidence that suggests that crystal structure studies alone may miss drugbinding pockets on mutant K-Ras surface 18,[25][26][27][28][29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 P NMR and X-ray crystallographic data from Shima et al ., 6971 together with MD simulations from our group, 152 showed that GppNHp-bound H-Ras in solution contains two interconverting conformations, “inactive” state 1 and “active” state 2; the former has a weak binding affinity for effector proteins, while the latter has a strong binding affinity for effector proteins. 68,153 31 P NMR spectroscopy revealed that the conformational ensemble of GppNHp-bound H-Ras in solution shifts towards the weak binding state 1 upon binding of Zn 2+ –1,4,7,10-tetraazacyclodecane (Zn 2+ –cyclen, 2 ) (Fig.…”
Section: Allosteric Inhibition Of Ras By Targeting Its Allosteric Smentioning
confidence: 98%